Inositol and herbal substances as elements of complementary therapy in patients with PCOS - Arkadiusz Aab; Julia Zarańska; Kamila Kędra; Izabela Michalik; Maciej Bielak; Bartosz Zarański (Journal of Education, Health and Sport, 2023)
Introduction: Polycystic ovary syndrome is a common hormonal disorder in women and the leading cause of female infertility. Traditional therapeutic methods often do not yield the expected results, hence the need to explore new treatment strategies. Promising results have been observed in studies on inositol.